Machine-music in Preschool Education. How to Provide Music Experience with Classics? - Edit Barta-Góhér (Multidisciplinary Journal of School Education, 2019)
Our ancestors’ cultural heritage should be passed down to all generations. This process can begin as early as the preschool age. The materials of music-listening in preschool education can be performed by the teachers. In this age, music experience is more etective and long lasting if children can see personally the performer as well. The development of the technical instruments nowadays, however, gives us the opportunity to listen to records of good quality in kindergartens. Children may receive no other valuable compositions, and most preschool teachers need help in the selection. This study’s ambition is to give some recommendations in this veld. Several opuses have been selected to complement certain activities of project pedagogy. The study also shows other possible usages by providing supplements on music history, form and the style characters of the passages, as well as assistance in achieving favourable outcomes in relation to music-listening with methodological advices. The selected projects – clock and spring – represent important knowledge, and with the experience given by music-listening we are able to bring these topics closer to children. Another important area of preschool education is listening to stories and the learningof stories. When tales are dramatized, all branches of arts can be linked together. A carefully selected passage of music may help to create a more impressive performance for the stories.